The Effect of the Group Investigation Learning Model on High School Grade X Students' Analytical Thinking Skills and Learning Outcomes on Environmental Pollution Subject - Ittaqi, Nabila; Wardani, Imaniah Bazlina (Aspirasi Masyarakat Intelektual Islam Nusantara, 2024)
Indonesian students' science skills are generally low, ranking 71st out of 79 countries in the 2018 PISA survey. Interviews with biology teachers at Jenggawah State Senior High School found that many students struggle with problem-solving and can't explain their answers well, despite having theoretical knowledge. To improve this, education should focus more on student-centered learning. One effective method is using the group investigation learning model, which can boost students' analytical thinking skills and improve their grades. The objective of this study is to assess the impact of the Group Investigation instructional model on the critical thinking skills of students, as well as the academic performance of grade X students in relation to environmental pollution. The research employed a quantitative methodology, specifically utilizing a quasi experimental design known as nonequivalent control group design. The sample approach employed was purposive sampling, where class X6 was chosen as the experimental group and X5 as the control group in Jenggawah state senior high school. Data gathering strategies employ assessment methods such as multiple-choice quizzes and essay writing. The Z test is employed as the data analysis approach. The research findings indicate a significant impact of the Group Investigation learning model on students' analytical thinking skills, with a significant p-value of 0.012. In addition, it was discovered that the Group Investigation learning model had also a significant impact on student learning outcomes, as shown by a significant value of 0.004.